Randomized clinical trial of trapezius squeezing test and jaw thrust as optimal indicators for Laryngeal mask airway insertion in adults under propofol anesthesia - Khanal, Sushil; Shrestha, Bibhush; Amatya, Roshana; Marhatta, Moda Nath (Journal of Society of Anesthesiologists of Nepal, 2016)
Background: Laryngeal mask airway insertion requires a certain depth of anesthesia that blunts the airway reflexes. We compared the effectiveness of the trapezius squeezing test with that of the jaw thrust test as clinical indicators of adequate condition for laryngeal mask airway insertion in adults under propofol anesthesia. Methods: In this randomized study, seventy adult patients undergoing surgery with general anesthesia maintained with laryngeal mask airway were randomly allocated to the group T (trapezius squeezing, n = 35) or the group J (jaw thrust, n = 35). The laryngeal mask airway was inserted immediately after the loss of response to trapezius squeezing or jaw thrust. We recorded successful and unsuccessful attempts. An unsuccessful attempt was defined as development of coughing, SPO2 < 90%, body movements during or within one minute of laryngeal mask airway insertion and failed insertion of laryngeal mask airway. Preparation time for laryngeal mask airway insertion, blood pressure, and heart rate were recorded. Results: The incidence of successful attempts was significantly higher in the group T than in the group J (p-value = 0.002). The time taken for preparation and insertion of laryngeal mask airway, arterial blood pressure and heart rate were comparable in both the groups. Conclusion: This study has demonstrated that the trapezius squeezing test is a superior indicator of an adequate condition for laryngeal mask airway insertion compared to the jaw thrust test in adults.